Her perfect life ebook - Ryan, Hank Phillippi (2021)
The next thrilling standalone novel by USA Today bestselling author Hank Phillippi Ryan . Everyone knows Lily Atwood—and that may be her biggest problem. The beloved television reporter has it all—fame, fortune, Emmys, an adorable seven-year-old daughter, and the hashtag her loving fans created: #PerfectLily. To keep it, all she has to do is protect one life-changing secret. Her own. Lily has an anonymous source who feeds her story tips—but suddenly, the source begins telling Lily inside information about her own life. How does he—or she—know the truth? Lily understands that no one reveals a secret unless they have a reason. Now she's terrified someone is determined to destroy her world—and with it, everyone and everything she holds dear. How much will she risk to keep her perfect life? At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.